Effects of a viscous-fibre supplemented evening meal and the following un-supplemented breakfast on post-prandial satiety responses in healthy women - Yong, M.; Solah, Vicky; Johnson, Stuart; Meng, X.; Kerr, Deborah; James, Tony; Fenton, Haelee; Gahler, R.; Wood, S. (2016)
The post-prandial satiety response and “second-meal effect” of a viscous fibre supplement PolyGlycopleX® (PGX®) was evaluated in a single-blind, randomised controlled crossover study of 14 healthy adult women. The two hour post-prandial satiety response, expressed as the area under the curve (AUC) of perceived hunger/fullness score versus post-prandial time, of a standardised evening meal with concurrent intake of either PGX softgel or rice flour softgel (control) was determined. On the following morning, after an overnight fast, the four hour satiety response to a standardised breakfast with no softgel supplementation was assessed. A significantly higher satiety response (AUC) to the standard dinner for the PGX-supplemented dinner compared with the control dinner (p = 0.001) was found. No significant difference (p = 0.09) was observed in the satiety response (AUC) of the breakfast regardless of which supplemented-dinner had been consumed prior, however the p value indicated a trend towards a higher response to the breakfast following the PGX-supplemented dinner. The fullness scores of the breakfast following the PGX-supplemented dinner at 15, 30, 90, 120, 150, 180, 210 and 240 min post-prandial were significantly higher than those for the breakfast following the control dinner (p = < 0.001, 0.007, 0.009, 0.009, 0.049, 0.03, 0.003 and < 0.001 respectively). PGX supplementation at dinner increased the satiety effects of both the dinner itself and the subsequent un-supplemented breakfast; a “second meal effect” indicting the potential for this fibre supplement to induce extended satiety.